2018
DOI: 10.34019/2596-3325.2018.v19.24714
|View full text |Cite
|
Sign up to set email alerts
|

Uso de extrato aquoso de pimenta malagueta (Capsicum frutescens L.) em testes de sobrevivência sobre Achatina fulica (Bowdich, 1822) (Mollusca, Gastropoda)

Abstract: Achatina fulica (Bowdich, 1822) é um molusco pulmonado terrestre originário do Leste-Nordeste da África, que se disseminou por todo o mundo, como praga agrícola e hospedeiro de várias doenças de interesse médico-veterinário, Foi introduzido no Brasil por volta de 1980 por criadores do Paraná, visando substituir o escargot Helix aspersa (Müller, 1774), embora exista relato da introdução desse molusco na Região Sudeste por volta da década de 1970. Com o insucesso na comercialização dessa espécie, foi solto no am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 17 publications
1
4
0
5
Order By: Relevance
“…The authors obtained an LD 50 of 39.160 ppm in 96 h. However, when compared to the concentration obtained in the promising result reported by Silva Júnior et al ( 2018), of 2,000 ppm, Rao and Singh (2000) showed a significant reduction in oviposition and viable egg production. However, the concentration used was 25.000 ppm, which when compared with the result obtained by Silva Júnior et al (2018), this treatment also reveals a high concentration. Rao and Singh (2002) described that the best LC 50 obtained after 96 h of testing for the binary combination of C. deodara oil + A. sativum bulb powder was 4.300 ppm, with an even higher concentration compared with Silva Júnior et al ( 2018).…”
Section: Quali-quantitative Analysissupporting
confidence: 48%
See 3 more Smart Citations
“…The authors obtained an LD 50 of 39.160 ppm in 96 h. However, when compared to the concentration obtained in the promising result reported by Silva Júnior et al ( 2018), of 2,000 ppm, Rao and Singh (2000) showed a significant reduction in oviposition and viable egg production. However, the concentration used was 25.000 ppm, which when compared with the result obtained by Silva Júnior et al (2018), this treatment also reveals a high concentration. Rao and Singh (2002) described that the best LC 50 obtained after 96 h of testing for the binary combination of C. deodara oil + A. sativum bulb powder was 4.300 ppm, with an even higher concentration compared with Silva Júnior et al ( 2018).…”
Section: Quali-quantitative Analysissupporting
confidence: 48%
“…In this study, phenolic compounds, tannins, flavonoids, and alkaloids were found in the C. frutescens aqueous extract. Saponins and anthraquinones were not found in the extract (Silva Júnior et al, 2018). In the other articles, no data from phytochemical analyses were found.…”
Section: Phytochemical Analysismentioning
confidence: 89%
See 2 more Smart Citations
“…O uso de substâncias de origem vegetal tem sido motivo de intensas pesquisas nos últimos anos, pois são biodegradáveis, causam menor impacto ambiental e podem ser de baixo custo (Ferreira et al, 2009(Ferreira et al, , 2010(Ferreira et al, , 2011Miranda et al, 2012), de modo que podem ser um importante material para o combate de moluscos pragas (Silva-Junior et al, 2018). Com isso, o objetivo deste estudo foi avaliar a influência da seiva de F. foetida no repertório comportamental e no horário de atividade de S. octona.…”
Section: 67unclassified